Green-Oriented Planning Example for the Rapidly Building City of Trabzon: KTU Kanuni Campus - Öztürk, Elif; Şen, Derya Elmalı (Bartın Üniversitesi, 2021)
One of the most important problems of our era is global warming and climate change. Rapidly building cities create heat islands, causing an increase in the impact of global warming and climate change. Supporting the natural environment and increasing the green texture in the cities is one of the most important tools in preventing the heat island effect. This study aims to research how to solve this problem in the city of Trabzon which is one of Turkey's rapidly building cities. Although Trabzon is one of the greenest cities in Turkey, there is lack of green space in downtown. Karadeniz Technical University Kanuni Campus was examined in order to find the answer whether the city can develop with a green-oriented design if this situation reversed. It was seen that the KTU Kanuni Campus, remained in the city center with the development of the city, was designed in harmony with the geography, topography and climate of the city in terms of basic settlement decisions and set a good example of green-oriented design.

Yaşadığımız çağın en önemli sorunlarından biri küresel ısınma ve iklim değişikliği sorunudur. Hızla yapılaşan kentler, ısı adaları oluşturarak küresel ısınma ve iklim değişikliğinin etkisinin artmasına sebep olmaktadır. Kentlerde doğal çevrenin desteklenmesi ve yeşil dokunun artırılması, ısı adası etkisinin giderilmesinde en önemli araçlardan biridir. Çalışmada, Türkiye'nin hızla yapılaşan kentlerinden biri olan Trabzon kentinde bu soruna nasıl çözüm üretilebileceğine dair bir araştırma yapmak hedeflenmiştir. Türkiye'nin en yeşil şehirlerinden biri olmasına karşın Trabzon kent merkezinin yeşil dokusu azdır. Bu durum tersine çevrilip yeşil odaklı bir tasarımla kent gelişebilir mi sorusuna yanıt olarak Karadeniz Teknik Üniversitesi Kanuni Kampüsü incelenmiştir. İncelemeler sonucunda şehrin gelişmesi ile kent merkezinde kalan KTÜ Kanuni Kampüsü'nün temel yerleşim kararları bakımından kentin coğrafi yapısı, topografyası ve iklimi ile son derece uyumlu tasarlandığı ve yeşil odaklı tasarıma iyi bir örnek teşkil ettiği görülmüştür.
Hızla Yapılaşan Trabzon Kenti İçin Yeşil Odaklı Planlama Örneği: KTÜ Kanuni Kampüsü
Keywords: Environmentally Sustainable Engineering; Çevresel Olarak Sürdürülebilir Mühendislik